Microbial Genetics: Foundations, Applications, and Future Directions in Science and Biotechnology - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammad (Darul Yasin Al Sys, 2025)
This field is essential to comprehending not just basic biological processes but also how they are used in biotechnology, agriculture, and medicine. Microbial genetics is the study of genetic material, which includes horizontal gene transfer, DNA replication, gene expression, and mutation. Many microorganisms, in contrast to larger species, have genomes that are small and relatively basic, enabling researchers to accurately examine the regulation and function of genes. Mechanisms like transformation, transduction, and conjugation, which speed up the acquisition and spread of genetic characteristics like antibiotic resistance, are primarily responsible for the genetic plasticity of microorganisms, especially bacteria. Given that existing treatment approaches are being challenged by the growth consequences. Additionally, using cutting-edge molecular methods like whole-genome sequencing, recombinant DNA technology, and CRISPR-Cas systems, microbial genetics aids in the creation of novel antibiotics, vaccines, and diagnostic instruments. The intricacies of microbial communities, or microbiomes, and their interactions with hosts and the environment have also been clarified by research in microbial genetics. Our knowledge of microbial ecology, pathogenicity, and symbiosis has increased as a result. The discipline is still developing in industrial settings, but the combination of systems genetics and computational biology holds promise for deciphering intricate regulatory networks and enabling predictive modeling of microbial behavior. As microbial genetics advances, ethical issues—especially those pertaining to gene editing and the discharge of genetically engineered organisms—become more significant. To sum up, microbial genetics is a fundamental component of contemporary biology and biotechnology, offering deep understanding of microbial life and laying the groundwork for advancement in a wide range of scientific and industrial domains. Addressing global health, sustainability, and environmental management concerns requires ongoing study in this area.